Quantification of Dexterity as the Dynamical Regulation of Instabilities: Comparisons Across Gender, Age, and Disease - Lawrence, Emily L.; Fassola, Isabella; Werner, Inge; Leclercq, Caroline; Valero-Cuevas, Francisco J. (Frontiers in Neurology, 2014)
Dexterous manipulation depends on using the fingertips to stabilize unstable objects. The Strength-Dexterity paradigm consists of asking subjects to compress a slender and compliant spring prone to buckling. The maximal level of compression (requiring low fingertip forces < 300 grams force, gf) quantifies the neural control capability to dynamically regulate fingertip force vectors and motions for a dynamic manipulation task. We found that finger dexterity is significantly affected by age (p=0.017) and gender (p=0.021) in 147 healthy individuals (66F, 81M, 20-88yrs). We then measured finger dexterity in 42 hands of older patients following treatment for osteoarthritis of the base of the thumb (CMC OA, 33F, 65.8±9.7yrs), and 31 hands from patients being treated for Parkinson’s disease (PD, 6F, 10M, 67.68±8.5yrs). Importantly, we found no differences in finger compression force among patients or controls. But we did find significantly stronger age-related declines in performance in the patients with PD (slope -2.7 gf/yr, p=0.002) than in those with CMC OA (slope -1.4 gf/yr, p=0.015), than in controls (slope -0.86 gf/yr). In addition, the temporal variability of forces during spring compression shows clearly different dynamics in the clinical populations compared to the controls (p< 0.001). Lastly, we compared dexterity across extremities. We found stronger age (p=0.005) and gender (p=0.002) effects of leg compression force in 188 healthy subjects who compressed a larger spring with the foot of an isolated leg (73F, 115M, 14-92yrs). In 81 subjects who performed tests with all four limbs, we found finger and leg compression force to be significantly correlated (females ρ=0.529 p=0.004, males ρ=0.403 p=0.003; 28F, 53M, 20-85yrs), but surprisingly found no differences between dominant and non-dominant limbs. These results have important clinical implications, and suggest the existence—and compel the investigation—of systemic vs. limb-specific mechanisms for dexterity.